2013
DOI: 10.1063/1.4818528
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ionization of the non-symmetric HeH+ molecule driven by intense ultrashort laser pulses

Abstract: We study enhanced single and double ionizations and enhanced single and double excitations in the nonsymmetric two-electron diatomic molecular ion HeH(+) in an intense ultrashort laser pulse linearly polarized along the internuclear axis (z axis). We solve a three-dimensional time-dependent Schrödinger equation, TDSE, via correlated two-electron ab initio calculations within the fixed-nuclei approximation. A complex scaling method is used for calculation of both single and double ionizations. These nonperturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
2
21
2
Order By: Relevance
“…An estimate of the characteristic time of this stretching motion can be done by the vibrational period associated to the v = 6 − 10 states, which is on the order of 34-100 fs or by the time a corresponding classical particle moves from R = 2 to R= 3.7 a.u., which is ≈12 fs. As a consequence, the ionization rate increases sharply for the stretched molecules [12], which induces molecular vibration and further ionization via the Lochfraß mechanism [25]. This mechanism is corroborated by the eyecatching lack of yield at KER= 8.5 eV (R = 3.1 a.u.)…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…An estimate of the characteristic time of this stretching motion can be done by the vibrational period associated to the v = 6 − 10 states, which is on the order of 34-100 fs or by the time a corresponding classical particle moves from R = 2 to R= 3.7 a.u., which is ≈12 fs. As a consequence, the ionization rate increases sharply for the stretched molecules [12], which induces molecular vibration and further ionization via the Lochfraß mechanism [25]. This mechanism is corroborated by the eyecatching lack of yield at KER= 8.5 eV (R = 3.1 a.u.)…”
mentioning
confidence: 72%
“…On the theory side, the solution of the time-dependent Schrödinger equation (TDSE) with all 9 degrees of freedom necessary to describe HeH + is extremely challenging and unfeasible with current computational resources. Therefore, approximations such as TDSE calculations with reduced dimensionality [12][13][14] or semiclassical approaches [15] are often used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism explains EI as the strong coupling of charge-resonant states at certain critical internuclear separation which then leads to an enhanced molecular ionization probability [14]. Studies by numerically solving the time-dependent Schrödinger equation (TDSE) show that EI persists in two-electron homo-and heteronuclear molecules [21][22][23][24][25][26]. An accurate description of EI is crucial for the understanding of nuclear kinetic energy release spectra following strong-field-induced dissociative ionization (see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,34,[47][48][49][50] For H + 2 and H 2 , it has been shown that charge resonance transitions and localization of the electronic wavefunction are responsible for this Charge-Resonance Enhanced Ionization (CREI) at critical internuclear distances. 47,48 Several numerical simulations have been carried out for the ionization of H + 2 as a function of bond length.…”
mentioning
confidence: 99%